2015
DOI: 10.5296/jee.v6i1.7892
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nutritional Status of School Children with and Without Mid Day Meal Programme

Abstract: <p>This cross sectional study was carried out to compare nutritional status amongst children of 14- 16 years age of three different sets of schools. Study was conducted at Private High School Campus (PHSC) without mid day meal programme, Govt. High School Hebbal (GHSH) with ISCKON mid day meal programme and Govt. High School Bashettahalli (GHSB) Doddaballapur, with Govt. mid day meal. Height, weight and body mass index (BMI) were measured. When height and weight of the study subjects compared with 50<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…This study found that 89.1% of children were normal in weight for age (WAZ) indices. Still, it was found only 33.9% normal children in Bangalore (Byadagi S, 2015), 53.28% normal children in Sirajgong (Hussein M, 2013), and only 16.0% were normal among the school-age slum children (Yeasmin S, 2016). This indicates that the prevalence of undernutrition was less at Sudarganj, Gaibandha.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that 89.1% of children were normal in weight for age (WAZ) indices. Still, it was found only 33.9% normal children in Bangalore (Byadagi S, 2015), 53.28% normal children in Sirajgong (Hussein M, 2013), and only 16.0% were normal among the school-age slum children (Yeasmin S, 2016). This indicates that the prevalence of undernutrition was less at Sudarganj, Gaibandha.…”
Section: Discussionmentioning
confidence: 99%